Entry barriers and tripartite evolutionary game analysis of seawater desalination under the government regulation in China - Chen, Mingbao; Xu, Zhibin; Wang, Yuhao (Frontiers in Marine Science, 2023)
Seawater desalination is a new promising marine industry and an important way to supplement the shortage of land water resources and promote the efficient use of seawater resources. Currently, the global desalination industry is rapidly developing. In China’s new development plan, large-scale development of the seawater desalination industry is also an important strategic goal. However, compared to the technological development of the seawater desalination industry, its marketization is affected by various factors, and its development level is still relatively low. Therefore, based on real industry data, this paper constructs a tripartite evolutionary game model for seawater desalination enterprises, water supply enterprises, and the government, and identifies several entry barriers for seawater desalination in China. The results include: (1) For seawater desalination to enter the market in China, government supervision limit should be no greater than 400,000 tons per day, about 13.8% of total seawater desalination scale. (2) The entry cost should be no more than 10 million yuan per day for seawater desalination, which is equivalent to approximately 18.25 trillion yuan during a five-year period. Finally, (3) political relatedness should be at least 2.0 for seawater desalination to take place, and 3.0 for it to develop in full swing. The paper also discusses the division of state- and foreign-owned water companies and reveals that government subsidies are only effective if foreign-owned companies seek rents. Based on the findings of the study, we propose pertinent policy recommendations including top-level planning, desalinated water infrastructure development, subsidy policy implementation, and public engagement. These recommendations aim to aid the Chinese government in fostering the desalination sector.